Barriers, facilitators and preferences for the physical activity of school children. Rationale and methods of a mixed study - Martínez-Andrés María; García-López Úrsula; Gutiérrez-Zornoza Myriam; Rodríguez-Martín Beatriz; Pardo-Guijarro María; Sánchez-López Mairena; Cortés-Ramírez Eugenio; Martínez-Vizcaíno Vicente (BMC, 2012)
Abstract Background Physical activity interventions in schools environment seem to have shown some effectiveness in the control of the current obesity epidemic in children. However the complexity of behaviors and the diversity of influences related to this problem suggest that we urgently need new lines of insight about how to support comprehensive population strategies of intervention. The aim of this study was to know the perceptions of the children from Cuenca, about their environmental barriers, facilitators and preferences for physical activity. Methods/Design We used a mixed-method design by combining two qualitative methods (analysis of individual drawings and focus groups) together with the quantitative measurement of physical activity through accelerometers, in a theoretical sample of 121 children aged 9 and 11 years of schools in the province of Cuenca, Spain. Conclusions Mixed-method study is an appropriate strategy to know the perceptions of children about barriers and facilitators for physical activity, using both qualitative methods for a deeply understanding of their points of view, and quantitative methods for triangulate the discourse of participants with empirical data. We consider that this is an innovative approach that could provide knowledges for the development of more effective interventions to prevent childhood overweight.